PENGUATAN INTEGRITAS PEMILU: PENDEKATAN INOVATIF MEMANFAATKAN MESIN PEMBELAJARAN UNTUK MENDETEKSI KECURANGAN - Komalasari, Rita; Mustafa, Cecep (Bawaslu Provinsi Jawa Barat, 2024)
This study explores the development and implementation of machine learning (ML) models designed to detect patterns indicating electoral fraud. The aim of this study is to address existing gaps in the literature by integrating advanced ML algorithms, leveraging various data sources, developing real-time monitoring systems, ensuring model transparency, and addressing ethical considerations. The main argument is that ML provides a robust and adaptive approach to enhance the accuracy and efficiency of detecting electoral fraud. This research employs a comprehensive analysis using Systems Theory to integrate and optimize the various components involved in detecting electoral fraud. The study also develops real-time monitoring systems and incorporates methods for model interpretability and transparency. Ethical and practical challenges are addressed through thorough analysis and the provision of guidelines for responsible implementation. The study demonstrates that machine learning significantly improves the detection of electoral fraud by identifying complex and subtle patterns that may be overlooked by traditional methods. The integration of various data sources and real-time monitoring enhances the resilience and timeliness of fraud detection. Ensuring model transparency and addressing ethical considerations helps build trust and accountability in the electoral process. Overall, this research provides a comprehensive solution that enhances the accuracy, efficiency, and trust in detecting electoral fraud, thereby supporting the integrity of the democratic process.